Pemberdayaan Masyarakat Melalui Pengembangan “Soft Skill Pembuatan Krupuk Paru Daun Singkong” dalam Upaya Peningkatan Pendapatan Masyarakat di Desa Tanjung Sanai Kabupaten Rejang Lebong - Ratna Wulan Sari; Isbandiyah Isbandiyah; Supriyanto Supriyanto (Jurnal Informasi Pengabdian Masyarakat, 2024)
As a woman who has skills but is sometimes not empowered due to limitations, in general, women in rural areas rely on work with rubber gardening, coffee and farming, by planting coffee and planting vegetables which usually wait a long time for them to harvest, and when they harvest, they are usually sold directly without them processing it into something that has food and generates additional income. So that a lot of time is wasted in vain. The purpose of this community service activity focuses on empowering village communities, especially women through the development of soft skills in making cassava leaf lung crackers in an effort to increase the income of the Tanjung Sanai village community in Rejang Lebong district. The purpose of this activity is to empower women by providing skills to women in Rejang Lebong Regency so that they can increase family income.